P2y12 inhibitor monotherapy after 1–3 months dual antiplatelet therapy in patients with coronary artery disease and chronic kidney disease undergoing percutaneous coronary intervention: a meta-analysis of randomized controlled trials - Yu, Yanqiao; Pan, Deng; Bai, Ruina; Luo, Jinwen; Tan, Yu; Duan, Wenhui; Shi, Dazhuo (Frontiers in Cardiovascular Medicine, 2023)
In patients with coronary artery disease (CAD) and chronic kidney disease (CKD) undergoing percutaneous coronary intervention (PCI), whether short-term dual antiplatelet therapy (DAPT) followed by P2Y12 inhibitors confers benefits compared with standard DAPT remains unclear. This study aimed to assess the efficacy and safety of 1-3 months of DAPT followed by P2Y12 monotherapy in patients with CAD and CKD undergoing PCI. PubMed, Embase, and the Cochrane Library were searched to identify randomized controlled trials (RCTs) comparing the P2Y12 inhibitor monotherapy after a 1-3 months DAPT versus DAPT in patients with CAD and CKD after PCI. The primary outcome was the incidence of major adverse cardiovascular events (MACEs), defined as a composite of all-cause mortality, myocardial infarction, stent thrombosis, target-vessel revascularization, and stroke. The safety outcome was the major bleeding events, defined as a composite of TIMI major bleeding or Bleeding Academic Research and Consortium (BARC) type 2, 3, or 5 bleeding. The pooled risk ratios (RRs) with 95% confidence intervals (CIs) were calculated with a fixed- or random-effects model depending on the heterogeneity among studies. Four RCTs including 20468 patients (2833 patients with CKD and 17635 without CKD) comparing P2Y12 inhibitor monotherapy with DAPT were included in our meta-analysis. Patients with CAD and CKD had higher risk of ischemic and bleeding events. P2Y12 inhibitor monotherapy after 1-3 months of DAPT significantly reduced the risk of major bleeding compared to DAPT in CKD patients (RR: 0.69, 95%CI: 0.51-0.95, P=0.02) and non-CKD patients (RR: 0.66, 95%CI: 0.49-0.89, P=0.01). No significant difference regarding MACEs between P2Y12 inhibitor monotherapy and DAPT was found in CKD patients (RR: 0.88, 95% CI: 0.59-1.31, P=0.53) and non-CKD (RR: 0.91, 95% CI: 0.79-1.04, P=0.17). P2Y12 inhibitor monotherapy after 1-3 months of DAPT was an effective strategy for lowering major bleeding complications without increasing the risk of cardiovascular events in patients with CAD and CKD undergoing PCI as compared with DAPT.